Efficient passage of competitive distances in academic rowing by taking into account the maximum strength indicators - Strykalenko, Y.; Shalar, O.; Huzar, V.; Voloshynov, S.; Homenko, V.; Bazylyev, S. (Journal of Physical Education and Sport, 2020)
The aim of the article is to explore the relationship between indicators of maximum strength and efficiency passage of distance in academic rowing on water and on the rowing simulator «Concept-2». Materials: 15 high qualification academic rowers participated in the study, among them were repeated participants of the European Championships, World Championships and the Olympic Games. Methods of studying strength and special preparedness of high sports qualification academic rowers included testing of their physical qualities, namely: lifting the barbell with arms in lying position, maximum acceleration on the rowing ergometer «Concept-2», horizontal thrust in the block Dyba simulator (full amplitude) and a final testing on the rowing simulator «Concept-2» at a 2000 m sports distance. Results: a high correlation dependence was found between the result of rowing on Concept at 6000 m and the result of competition on the water (r = 0,708), and also the average level of dependence between rowing on the ergometer at 2000m and the competition on the water (r = 0,579). The highest inverse correlation dependence was observed between the indicator of maximum acceleration on the rowing ergometer and strength tests (thrust lying down r = - 0,707 and thrust «Dyba» r = - 0,881). Those high indicators of strength qualities had a positive effect on speed acceleration of rowers. There is a low negative correlation connection between indicators of the test «Thrust lying down» and «Dyba» with the results of performances of athletes at competitions, r = - 0,189 and r = - 0,256, respectively. Conclusions: The low correlation connection between the maximum strength and the efficiency of competitive distance on water indicates that these indicators may not influence on the effectiveness of competitive distance on water sufficiently, as a rower does about 240 paddles during the competition. This requires the athlete has to show strength endurance. Also during rowing on water there are external factors (wind, waves, etc.), which in turn requires the athlete adapting to each paddle.